A remarkable new species of Salacia (Celastraceae: Salacioideae) from the Western Ghats, India. (21st April 2020) - Page, Navendu V.; Nandikar, Mayur D.
Abstract : A new species of Salacia is described from Karnataka and Kerala states of the Western Ghats, India. It is unique within the genus on account of its obliquely dehiscing anthers and 7–10 cm long, prolate to broadly ellipsoid or ovoid, keeled, greenish‐yellow 5‐ to 8‐seeded fruit with thin epicarp and dry mesocarp. Salacia megacarpa sp. nov. can be grouped with S. fruticosa Heyne ex M.A.Lawson and S. oblonga Wight & Arn. which are the only other species from the sub‐continent which exhibit axillary, ramiflorous, dichotomously branched cymes.